2015
DOI: 10.1111/jocn.12887
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with rushed and missed resident care in western Canadian nursing homes: a cross‐sectional survey of health care aides

Abstract: Considering the resident population in nursing homes today--many with advanced dementia and all with complex care needs--health care aides having enough time to provide physical and psychosocial care of high quality is a critical concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(130 citation statements)
references
References 33 publications
2
123
1
4
Order By: Relevance
“…The activities performed in the traditional UCP role include (i) support for ADLs—feeding, bathing, grooming, dressing, lifts and transfers, personal hygiene of oral, skin and nail care; (ii) instrumental activities of daily livings (IADLs)—menu and meal planning, meal preparation, transportation or accompanying patients, shopping, educational and recreational assistance; and (iii) light housekeeping (e.g., sweeping and mopping floors, vacuuming, washing dishes and laundry; Canadian Nurses Association, ; Community Care Access Centre (CCAC), ; Government of Alberta, ; Johnson & Noel, ; Knopp‐Sihota, Niehaus, Squires, Norton, & Estabrooks, ; Ontario Personal Support Workers Association, ; Sullivan & Sharpe, ; Suter et al., ; Zeytinoglu, Denton, Brookman, & Plenderleith, ).…”
Section: Resultsmentioning
confidence: 99%
“…The activities performed in the traditional UCP role include (i) support for ADLs—feeding, bathing, grooming, dressing, lifts and transfers, personal hygiene of oral, skin and nail care; (ii) instrumental activities of daily livings (IADLs)—menu and meal planning, meal preparation, transportation or accompanying patients, shopping, educational and recreational assistance; and (iii) light housekeeping (e.g., sweeping and mopping floors, vacuuming, washing dishes and laundry; Canadian Nurses Association, ; Community Care Access Centre (CCAC), ; Government of Alberta, ; Johnson & Noel, ; Knopp‐Sihota, Niehaus, Squires, Norton, & Estabrooks, ; Ontario Personal Support Workers Association, ; Sullivan & Sharpe, ; Suter et al., ; Zeytinoglu, Denton, Brookman, & Plenderleith, ).…”
Section: Resultsmentioning
confidence: 99%
“…The provision of individualized, holistic care is an important attribute and value in relation to nursing practice (Lusk & Fater, ). However, the time to provide centred nursing and healthcare is vanishing, replaced with a rushed, utilitarian approach that addresses the basic care necessities (Knopp‐Sihota, Niehaus, Squires, Norton, & Estabrooks, ). It has been suggested that if a healthcare provider cannot meet their perceived ethical responsibilities, or if their moral orientation is compromised, moral distress can result (Austin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Work in Canadian LTC homes has also been described as particularly task-oriented and role-differentiated (34). Nevertheless, resource constraints in LTC are well documented elsewhere (32,33), do appear to create time pressure (23,26,(34)(35)(36)(37), and have operated as a barrier to offering Namaste Care at the recommended intensity in prior studies (20). Indeed, given that similar concerns about LTC workload exist on a global scale, it may be helpful for homes implementing Namaste Care to plan for an additional staff member to cover the part of the day during which Namaste Care is offered.…”
Section: Discussionmentioning
confidence: 99%